The Effects of Lexical Tone Awareness on Early Word Recognition, Word Reading, and Spelling From Dictation of Thai Children: A Longitudinal Study - Thongseiratch, Therdpong; Kraiwong, Tuangporn; Roengpitya, Rungpat (Frontiers in Psychology, 2021)
In tonal languages such as Thai, lexical tone (the pitch of a syllable) affects word meaning. This study examined the effects of lexical tone awareness on early word recognition and the relationship between these abilities and word reading and spelling in subsequent grades. A longitudinal design was used to assess reading-related skills in 259 Thai children, first in kindergarten (130 girls, Mage = 67.25 months) and later in Grade 3 (Mage = 102.25 months). In kindergarten, the children were tested on lexical tone identification and differentiation, early literacy skills, non-verbal IQ, and early word recognition. In Grade 3, they were tested on word reading and spelling from dictation. The hierarchical regression analyses showed that the lexical tone identification skills in kindergarten accounted for 2% of the unique variance in early word recognition. However, none of the lexical tone awareness skills could predict word reading and spelling from dictation after controlling for other literacy-related skills. These findings suggest that lexical tone awareness skill positively associated with early word recognition at the kindergarten level, but not for word reading and spelling from dictation at a Grade 3 level.